2021
DOI: 10.38035/jlph.v1i3.56
|View full text |Cite
|
Sign up to set email alerts
|

Application of Business Ethics and Business Law on Economic Democracy that Impacts Business Sustainability

Abstract: Ethics and Business Law are identical to the rules and procedures for running our business by existing laws not to harm any party. An excellent economic activity, of course, has complied with the regulations that have been set. The implementation of an affair, trade, industry or related financial activity carried out by a business entrepreneur. Business Law can determine the progress of a company or other entrepreneur in implementing their performance because every company has different principles. Of course, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The environment influences decision making, this is in line with research conducted by: (F. Saputra & Saputra, 2021), (Maharani & Saputra, 2021), (Mahaputra & Saputra, 2021c), (Mahaputra & Saputra, 2021b), (Mahaputra & Saputra, 2021a), (F. Saputra, 2021).…”
Section: The Effect Of Environment On Decision Makingsupporting
confidence: 78%
“…The environment influences decision making, this is in line with research conducted by: (F. Saputra & Saputra, 2021), (Maharani & Saputra, 2021), (Mahaputra & Saputra, 2021c), (Mahaputra & Saputra, 2021b), (Mahaputra & Saputra, 2021a), (F. Saputra, 2021).…”
Section: The Effect Of Environment On Decision Makingsupporting
confidence: 78%
“…Work effectiveness is the completion of work on time, meaning that the implementation of a task is marked as good or not, it really depends on how to complete the task, and how much it costs. issued for that (Mahaputra & Saputra, 2021). From the understanding according to these experts, it can be concluded that work effectiveness is a completion of work that reaches the target or on time (Siti Maysita, 2016:236).…”
Section: Work Effectivenessmentioning
confidence: 99%
“…The organizing influence carried out by the principal aims to regulate and control the workforce, determine the performance of its employees to maximize school performance. Principals who have leadership in organizing are considered capable of managing the organization well, so that public trust in the school arises (Mahaputra & Saputra, 2021).…”
Section: The Effect Of Organizing On Principal Leadershipmentioning
confidence: 99%
“…2) Motivation: (F. Saputra, 2022b), (Octavia & Ali, 2017), (Larasetiati & Ali, 2019), (Fahmi & Ali, 2022), (Hernikasari et al, 2022), (Ali et al, 2016, (Wahono & Ali, 2021), (Iryani et al, 2021), (Hasyim & Ali, 2022), (Werita & Nofrialdi, 2021), (Desmiwerita & Saputra, 2019), (E. B. Saputra, 2022), (Hardiansyah et al, 2019), (F. Saputra & Saputra, 2021). 3) Decision Making: (Mahaputra & Saputra, 2021), (Kholisoh & Ali, 2020), (Fauzi & Ali, 2021), (Ali, Zainal, et al, 2022), (Suleman et al, 2020), (Maisharoh & Ali, 2020), , (Paijan & Ali, 2017), (Zulhendra & Nofrialdi, 2022). 4) Implementation: (F. Saputra & Ali, 2022), (Masruhin et al, 2021), (Suharyono & Ali, 2015), (Richardo et al, 2020), (Zahran & Ali, 2020), (Yassir Araffat et al, 2020), (Fardinal et al, 2022), (Haitao & Ali, 2022), (Gusfa et al, 2017), (Nofrialdi, 2022).…”
Section: Conceptual Frameworkmentioning
confidence: 99%